MORPHOLOGICAL AND FUNCTIONAL FEATURES OF THE TESTIS AND EPIDIDYMIS AFTER ELECTROMAGNETIC FIELD EXPOSUREAND THE USE OF A SOLUTION OF ECHINACEA - Sharapova, E.N.; Тоpka, E.G. (World of Medicine and Biology, 2012)
During work researched structure and functions of rats’ epididimis, which were radiated by high voltage low frequency electromagnetic field, while rats were given the solution of Echinacea. The authors had proved that using of immunomodulator solution increases the function of epididimis and testicles; it doesn’t cause fertilizing ability dysfunction of radiated males during the initial and late terms of the research observation.
Keywords: testis; epididimis; spermatic channel; spermatogonia; electromagnetic field